Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How to prove the following:

$$\int^\infty_{-\infty}\frac{\ln(t+1)}{t^2+1}\mathrm{d}t=\frac{\pi}{2}\left(\ln(2)+\frac{\pi}{2} i\right)$$

share|cite|improve this question
This doesn't make sense for $t \leq 1$ since you are taking the log of a negative number, unless you are specifying a certain branch cut. – nayrb Aug 24 '12 at 2:44
Are you trying to evaluate a real integral of a complex non-real function? Perhaps it was meant to be $\,\log|t+1|\,$? – DonAntonio Aug 24 '12 at 2:57
up vote 6 down vote accepted

Deform the contour to pick up the residue at $t=i$, $$\begin{eqnarray*} \int^\infty_{-\infty}\frac{\ln(t+1)}{t^2+1}\mathrm{d}t &=& 2\pi i\, \mathrm{Res}_{t=i} \frac{\ln(t+1)}{t^2+1} \\ &=& 2\pi i \frac{\ln(1+i)}{2i} \\ &=& \frac{\pi}{2}\left(\ln 2+\frac{\pi}{2} i\right). \end{eqnarray*}$$ Here we have assumed the cut starting at $t=-1$ is slightly below the original contour. This appears to be the intended assumption. (If we instead assume the cut is slightly above the original contour we pick up the residue at $t=-i$ and get the complex conjugate of the quoted result.)

Note that the contribution at infinity vanishes since it goes like $\ln(R)/R\,(R\to\infty)$.

share|cite|improve this answer
A delightful answer! (+1) :D – user 1618033 Aug 30 '12 at 6:35

Let's evaluate the real and imaginary parts of the integral separately. Using $\Re(\ln(t+1)) = \ln(|t+1|)$ and $\Im(\ln(t+1)) = \pi [t < -1]$, where $[t<1]$ is the Iverson bracket: $$ \begin{eqnarray} \Re \int_{-\infty}^\infty \frac{\ln(t+1)}{t^2+1} \mathrm{d} t &=& \int_{-\infty}^\infty \frac{\ln(|t+1|)}{t^2+1} \mathrm{d} t = \frac{1}{2} \int_{-\infty}^\infty \frac{\ln((t+1)^2 )}{t^2+1} \mathrm{d} t\\ \Im \int_{-\infty}^\infty \frac{\ln(t+1)}{t^2+1} \mathrm{d} t &=& \int_{-\infty}^{-1} \frac{\pi}{t^2+1} \mathrm{d} t \end{eqnarray} $$ The integral for the imaginary part is easy, since $\int \frac{\mathrm{d} t}{t^2+1} = \arctan(t) + C$: $$ \int_{-\infty}^{-1} \frac{1}{t^2+1} \mathrm{d} t = \left.\arctan(t)\right|_{-\infty}^{-1} = \arctan(-1) - \lim_{t\to -\infty} \arctan(t) = -\frac{\pi}{4} - \left(-\frac{\pi}{2}\right) = \frac{\pi}{4} $$ Now to the real part: $$ \int_{-\infty}^\infty \frac{\frac{1}{2} \log((t+1)^2)}{t^2+1} \mathrm{d} t = \int_{-\infty}^\infty \frac{\frac{1}{2} \log(t^2)}{t^2-2t +2} \mathrm{d} t = \int_0^\infty \log(t^2) \frac{1}{2} \left( \frac{1}{(t-1)^2+1}+\frac{1}{(t+1)^2 + 1} \right) \mathrm{d} t = \int_0^\infty \log(t^2) \frac{t^2+2}{t^4+4} \mathrm{d} t \stackrel{u=t^2}{=} \int_0^\infty \frac{\log(u)}{2} \frac{u+2}{u^2+4} \frac{\mathrm{d} u}{\sqrt{u}} = \frac{1}{2} \left.\frac{\mathrm{d} }{\mathrm{d} s} \int_0^\infty u^{s-1} \frac{u+2}{u^2 + 4} \mathrm{d} u \right|_{s=\frac{1}{2}} $$ The latter integral is a sum of Mellin-Barnes transforms of $\frac{1}{u^2+4}$: $$ \int_0^\infty u^{s-1} \frac{u+2}{u^2 + 4} \mathrm{d} u = 2 \int_0^\infty u^{s-1} \frac{1}{u^2 + 4} \mathrm{d} u + \int_0^\infty u^{s} \frac{1}{u^2 + 4} \mathrm{d} u = \frac{2^{s-2} \pi}{\sin\left(\frac{\pi s}{2}\right)} + \frac{2^{s-2} \pi}{\cos\left(\frac{\pi s}{2}\right)} $$ Differentiating, and setting $s=\frac{1}{2}$ yields the result: $$ \int_{-\infty}^\infty \frac{\frac{1}{2} \log((t+1)^2)}{t^2+1} \mathrm{d} t = \pi \log(2) $$ Recombining the real and imaginary parts: $$ \int_{-\infty}^\infty \frac{\ln(t+1)}{t^2+1} \mathrm{d} t = \pi \log(2) + i \frac{\pi^2}{4} $$

share|cite|improve this answer

It would be easier if you define $$I(\alpha)=\int_{-\infty}^\infty\frac{\ln(\alpha t+1)}{t^2+1}dt.$$ Then \begin{eqnarray*} I'(\alpha)&=&\int_{-\infty}^\infty\frac{t}{(\alpha t+1)(t^2+1)}dt\\ &=&\frac{1}{\alpha^2+1}\int_{-\infty}^\infty\left(-\frac{1}{t+\frac{1}{\alpha}}+\frac{t}{t^2+1}+\frac{\alpha}{t^2+1}\right)dt\\ &=&\frac{1}{\alpha^2+1}\left(-\ln\frac{t+\frac{1}{\alpha}}{\sqrt{t^2+1}}+\alpha\arctan t\right)\big|_{-\infty}^\infty\\ &=&\frac{1}{\alpha^2+1}\left[\ln(-1)+\alpha\pi\right]\\ &=&\frac{\pi}{\alpha^2+1}(i+\alpha), \end{eqnarray*} and hence $I(\alpha)=\pi i\arctan\alpha+\frac{\pi}{2}\ln(\alpha^2+1)+C$. But $I(0)=0$ implies $C=0$. Thus $$I(1)=\pi i\frac{\pi}{4}+\frac{\pi}{2}\ln 2=\frac{\pi}{2}\left(\ln 2+i\frac{\pi}{2}\right).$$

share|cite|improve this answer

A related problem. Making the change of variables $t=u-1$ yields, $$ \int^\infty_{-\infty}\frac{\ln(t+1)}{t^2+1}\mathrm{d}t = \int _{-\infty }^{0 }\!{\frac {\ln \left( u \right) }{2+{u}^{2}- 2\,u}}{du} + \int _{0 }^{\infty }\!{\frac {\ln \left( u \right) }{2+{u}^{2}- 2\,u}}{du} $$

The last integral has no problem, since $\ln(u)$ is real. For the other integral, we use the substitution $u=-z$, $$ \int _{-\infty }^{0 }\!{\frac {\ln \left( u \right) }{2+{u}^{2}- 2\,u}}{du} = \int _{0}^{\infty }\!{\frac {\ln \left( z \right)+\ln(-1) }{2+{z}^{2}+2\,z}}dz $$ That implies that

$$ \int _{-\infty }^{\infty }\!{\frac {\ln \left( u \right) }{2+{u}^{2}- 2\,u}}{du} = \int _{0 }^{\infty }\!{\frac {\ln \left( u \right) }{2+{u}^{2}- 2\,u}}{du} + \int _{0}^{\infty }\!{\frac {\ln \left( z \right) }{2+{z}^{2}+2\,z}}dz +\int _{0}^{\infty }\!{\frac {\ln(-1) }{2+{z}^{2}+2\,z}}dz$$ $$ = \frac{3\pi\ln(2)}{8} + \frac{\pi\ln(2)}{8}+\ln(-1)\,\frac{\pi}{4} $$ Now using $ \ln(-1)=i\pi $ the result follow $$ \frac{\pi \ln(2)}{2} + \frac{i\pi^2}{4} = \frac{\pi}{2}\left(\ln(2)+\frac{\pi}{2} i\right) $$

share|cite|improve this answer
How did you move from this $ \int _{-\infty }^{\infty }\!{\frac {\ln \left( u \right) }{2+{u}^{2}- 2\,u}}{du} = \int _{0 }^{\infty }\!{\frac {\ln \left( u \right) }{2+{u}^{2}- 2\,u}}{du} + \int _{0}^{\infty }\!{\frac {\ln \left( z \right) }{2+{z}^{2}+2\,z}}dz +\int _{0}^{\infty }\!{\frac {\ln(-1) }{2+{z}^{2}+2\,z}}dz$ to this $ = \frac{3\pi\ln(2)}{8} + \frac{\pi\ln(2)}{8}+\ln(-1)\,\frac{\pi}{4} $? – Frank Aug 24 '12 at 18:50
@MohammedAl-mubark: In the step where I applied the transformation $u=-z$, you get $\ln(u)=\ln(-z)=\ln(-1)+\ln(z)$ by the properties of the $\ln$ function. – Mhenni Benghorbal Aug 25 '12 at 3:26
But how did you get the result of $\int _{0}^{\infty }\!{\frac {\ln \left( z \right) }{2+{z}^{2}+2\,z}}dz +\int _{0}^{\infty }\!{\frac {\ln(-1) }{2+{z}^{2}+2\,z}}dz$? – Frank Aug 25 '12 at 11:31
@MohammedAl-mubark:See here; – Mhenni Benghorbal Aug 30 '12 at 17:09

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.